Effects of Economic Growth, Electricity Consumption, Energy Use, and Urbanisation on Carbon Dioxide Emissions in Vietnam - Anh Tru Nguyen (Asian Academy of Management Journal, 2023)
The aim of this paper was to explore the causal relationship between CO2 emissions, economic growth, electricity consumption, energy use, and urbanisation in Vietnam between 1982 and 2016 using the Vector Error Correction Model (VECM). In the short run, it has been empirically proven that GDP, electricity consumption, and energy use have significant and positive relationships with CO2 emissions in Vietnam. Results also indicated that electricity consumption and energy use are the main contributors to increase GDP while CO2 emissions and urban population negatively affect GDP. It was also found that GDP has a significant and negative impact on electricity consumption, but energy use positively affects electricity consumption in Vietnam. Further, urban population has a negative influence on energy use, while the latter has a positive relationship with urban population. In the long run, results showed that GDP per capita and energy use per capita have significant and positive influence on CO2 emissions in Vietnam while urban population contributes to reducing CO2 emissions. The results of the Johansen co-integration test showed that there is a long run relationship between CO2 emissions, economic growth, electricity consumption, energy use, and urbanisation. Results implied that economic growth should be considered by the Vietnamese government along with the target in environmental protection, and urbanisation should be carefully managed to achieve sustainable development in Vietnam.